Aleister Crowley: Art, Sex, and Magick in the Weimar Republic - Churton, Tobias (Inner Traditions International, Limited, 2014)
Aleister Crowley arrived in Berlin in 1930 at a time when the city played host to many of the world's outstanding artists, philosophers, and scientists, including Einstein, Brecht, Huxley, and Isherwood. Drawing on unpublished material, Tobias Churton examines Crowley's years in Weimar Berlin, revealing "The Beast" to be a man of art and thought, a Crowley long hidden from the historical record.